TXNRD1 Is an Unfavorable Prognostic Factor for Patients with Hepatocellular Carcinoma. (27th April 2017) - Fu, Binsheng; Meng, Wei; Zeng, Xiancheng; Zhao, Hui; Liu, Wei; Zhang, Tong
Abstract : Thioredoxin reductase 1 (TXNRD1) which is a selenocysteine-containing protein is overexpressed in many malignancies. Its role in the hepatocellular carcinoma (HCC) prognosis has not been investigated. In this study, we investigated whether TXNRD1 functions as an independent prognostic factor for HCC patients. We found TXNRD1 was overexpressed in HCC tissues and cells, immunohistochemical analysis suggested TXNRD1 was elevated in 57 of 120 (47.5%) clinical samples, and its level was increased with the increasing clinical stage. In addition, TXNRD1 expression was positively correlated with clinical stage (p = 3.5 e - 5 ), N classification (p = 4.4 e - 4 ), and M classification (p = 0.037 ) of HCC patients. Kaplan-Meier analysis revealed that patients with high TXNRD1 expression had significantly shorter survival time than patients with low TXNRD1 expression. Multivariate analysis found TXNRD1 was an independent prognostic factor for HCC patients. In conclusion, our data suggested that TXNRD1 was a biomarker for the prognosis of patients with HCC.